VIRTUAL REALITY MENTAL REHABILITATION - HAWAZIL, HAIZA SHAZLEEN (IRC, 2020)
Mental stress can be considered as one of the critical issues experienced by university students, lecturers, people with career and other people which may affect their body, thoughts, behavior, and feelings. In these day and age, there are several people who are affected by this serious mental health and do not seek for help which then may lead them to committing suicide. Virtual Reality Therapy (VRT) is a forthcoming strategy for mental stress treatment which allows the interaction of the participants with an immersive three-dimensional virtual environment. This study explored on the application of virtual reality using forest nature-based therapy and the effect of the application on the students, lecturers, employees and many more. Forest nature-based therapy initiated as a nature-based intercession that aims on particular people with mental health and physical health issues which assimilates outdoor components such as forests, flowers, animals and other natural elements in the stress therapy process. This therapy will give positive impacts on a person’s health, improves psychological wellbeing and increase spiritual enhancement. The proposed solution is expected to help the targeted participants in coping and reducing their stress level and live a healthy life.